A phantom study: Evaluation of a novel three-lumen balloon catheter for potential treatment of intractable limb ischemia. (May 2023) - Tatarlar, Efecan; Yusuf, Emir; Kocatürk, Özgür
Abstract: Critical limb ischemia (CLI) is the most severe form of peripheral arterial disease (PAD) which induces extremity rest pain, extremity gangrene or ulcers that mostly might lead to limb loss. One of the most common criteria of CLI is 50 mmHg or less systolic ankle arterial pressure. In this study, a custom made three-lumen catheter (9 Fr) including a distal inflatable balloon in between the inflow and outflow lumen holes was designed and fabricated based on the patented design of Hyper Perfusion Catheter. The proposed catheter design aims to increase ankle systolic pressure to 60 mmHg or more to promote healing and/or alleviating severe pain due to intractable ischemia for patients with CLI. To simulate the blood circulation of related anatomy, in vitro CLI model phantom was designed and constructed by using a modified hemodialysis circuit, a hemodialysis pump and a tube set for cardio-pulmonary bypass surgery. A blood mimicking fluid (BMF) with dynamic viscosity of 4.1 mPa.s was used at 22 ºC to prime the phantom. The data was collected by a custom-made circuit design in real time and all measurements were verified with commercial certificated medical devices. The results of in vitro CLI model phantom experiments have shown that it is feasible to elevate the pressure distal to the occlusion (representing ankle pressure) above 80 mmHg without affecting the systemic pressure. Highlights: With current methods untreatable CLI results in amputation of the limb 5. Ankle systolic pressure is most important determinant in the viability of the limb 6. The proposed catheter design aims to increase ankle pressure to 60 mmHg or more 7. A phantom model is created to simulate compromised arterial circulation 8. The target ankle systolic pressure (>60 mmHg) is achieved in the phantom model experiments 9.